2000
DOI: 10.1074/jbc.m000756200
|View full text |Cite
|
Sign up to set email alerts
|

A Conformation Change in the Carboxyl Terminus of Alzheimer's Aβ(1–40) Accompanies the Transition from Dimer to Fibril as Revealed by Fluorescence Quenching Analysis

Abstract: Alzheimer's disease is characterized by the presence of insoluble, fibrous deposits composed principally of amyloid ␤ (A␤) peptide. A number of studies have provided information on the fibril structure and on the factors affecting fiber formation, but the details of the fibril structure are not known. We used fluorescence quenching to investigate the solvent accessibility and surface charge of the soluble A␤(1-40) dimer and amyloid fibrils. Analogs of A␤(1-40) containing a single tryptophan were synthesized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 31 publications
(32 reference statements)
4
47
3
Order By: Relevance
“…Although it is not yet clear that molten oligomeric species are obligate intermediates in the formation of other amyloids (as it is for NM), they are present in the initial stages of many amyloid assemblies 43,44 . Evidence also attests to the importance of dimeric interactions in the assembly of diverse amyloids [45][46][47] . Recent molecular dynamics simulations with Ab peptide suggest that assembly begins with a molten oligomeric species that allows the rapid sampling of multiple intermolecular contacts, with two individual molecules precipitously finding the right contact and nucleating assembly 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not yet clear that molten oligomeric species are obligate intermediates in the formation of other amyloids (as it is for NM), they are present in the initial stages of many amyloid assemblies 43,44 . Evidence also attests to the importance of dimeric interactions in the assembly of diverse amyloids [45][46][47] . Recent molecular dynamics simulations with Ab peptide suggest that assembly begins with a molten oligomeric species that allows the rapid sampling of multiple intermolecular contacts, with two individual molecules precipitously finding the right contact and nucleating assembly 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Trp substitution in these positions is not expected to have much effect on the overall hydrophobicity and net charge of the protein. Moreover, substitution of Val with Trp has been previously used effectively to study site-specific conformational changes in A␤ protein (associated with Alzheimer disease) during its aggregation (64). The C-terminal substitution A124W and A140W are also reported not to change the structural properties of ␣-Syn and have been used previously for studying the structural features of ␣-Syn oligomers (59).…”
Section: Site-specific Structural Dynamics Of ␣-Syn In Its Solublementioning
confidence: 99%
“…For proteins, such intrinsic signals are essentially restricted to tyrosine and tryptophan residues. Recently some studies (19,20) showed similar approaches for other amyloids. Tau contains 5 Tyr residues but no Trp.…”
mentioning
confidence: 99%